2011
DOI: 10.1002/mnfr.201100513
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenetics of the lipoprotein metabolism

Abstract: It is well known that lipid metabolism is a cornerstone in the development of the commonest important chronic diseases worldwide, such as obesity, cardiovascular disease, or metabolic syndrome. In this regard, the area of lipid and lipoprotein metabolism is one of the areas in which the understanding of the development and progression of those metabolic disorders has been studied in greater depth. Thus, growing evidence has demonstrated that while universal recommendations might be appropriate for the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 87 publications
0
12
0
3
Order By: Relevance
“…Food groups contributing to dietary patterns are not consistent across populations, which may yield discrepant results in dietary pattern studies among different populations [12]. The gene-diet interaction has helped to shed more light on an understanding of this variability, an area that has been poorly explored [6,13]. Baylin et al [14] reported that Samoans adhering to modern dietary patterns have high TG levels if they are homozygous for the rs9308762 C allele.…”
Section: Introductionmentioning
confidence: 99%
“…Food groups contributing to dietary patterns are not consistent across populations, which may yield discrepant results in dietary pattern studies among different populations [12]. The gene-diet interaction has helped to shed more light on an understanding of this variability, an area that has been poorly explored [6,13]. Baylin et al [14] reported that Samoans adhering to modern dietary patterns have high TG levels if they are homozygous for the rs9308762 C allele.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that because ε4 allele carriers present higher levels of serum total cholesterol and LDL-C, they are more likely to develop CVD compared to carriers of other alleles [25]. In a study with Brazilian individuals, it was found that the risk of dyslipidemia was three times greater in subjects carrying ε4 allele when compared to ε2 carriers [26].…”
Section: Nutrigenetic Basesmentioning
confidence: 98%
“…It is estimated that 60% of the differences observed in serum cholesterol levels between different individuals are related to genetic determinants, including SNPs in genes of enzymes, transporters, and apolipoproteins. It is important to highlight that 14% of those differences are defined by the SNPs APOE rs429358 and rs7412 [24,25]. The SNPs APOE rs429358 + rs7412 results from two variations in exon 4 of the gene, which cause changes that are differentiated by the cysteine and arginine content at codons 112 and 158, respectively.…”
Section: Nutrigenetic Basesmentioning
confidence: 99%
“…It is generally accepted that the impact of dietary fat on postprandial lipoprotein response differs between individuals, and genetic factors are thought to be one of the key determinants of such inter-individual variability. Nutrigenetics of postprandial lipid metabolism including evidence from human dietary interventions has recently been reviewed [122,123]. …”
Section: Nutrigenetics and Metabolic Diseasementioning
confidence: 99%